Sculpture Contemporaine. - Centre Culturel de Péruwelz (Bruxelles : Ministère de la Culture Française, 1969)
Arnould, Marcel ; Baivier, Jacques ; Baudart, Théo ; Boulanger, Michel ; Caille, Pierre ; Courtois, Albin ; Gangolf, Serge ; Ghysels, Jean-Pierre ; Grard, George ; Guebels-Dervichian, Monique ; Guilmot, Jacques ; Hambye, Damien ; Hardy, André ; Joly, Maurice ; Laenen, Jean-Paul ; Leroy, Christian ; Moeschal, Jacques ; Point, Jean-Pierre ; Roulin, Félix ; Snoeck, Alphonse ; Stievenart, Michel ; Van Albada, Henri ; Willame, Jean ; Willequet, André
Sculpture Contemporaine, Centre Culturel de Péruwelz, Parc Petit, Péruwelz, 23.8 - 26.10.1969
boek